The role of MRI diffusion and morphological parameters in diagnostic of local recurrence of posteoperative pancreatic adenocarcinoma proven by PET/CT - Saponjski, Dusan; Sobic Saranovic, Dragana; Đurić Stefanović, Aleksandra (Medicinski podmladak, 2023)
Pancreatic adenocarcinoma is one of the most common malignant diseases today with a high mortality rate. The disease is asymptomatic for a long period or causes non-specific symptoms as nausea, pain and symptomatically icterus. It is why it is most often discovered in the later stages. The only available curative method is a radical surgical intervention, which involves the Whipple procedure for tumors localized in the area of ​​the head of the pancreas or distal pancreatectomy in case the tumor is localized in the region of the body or tail.Given the fact that most tumors are discovered in an advanced form of the disease, a small number of patients are candidates for surgical intervention and even after the same, and the five-year survival rate is relatively low. For this reason, early detection of local recurrence is of great importance. In daily work so far, PET-CT has proven to be the method of choice for early detection of local recurrence. More and more studies show the importance of MR and diffusion sequences in diagnosing recurrence of pancreatic cancer.